The Correlation Between Body Mass Index and Random Blood Sugar Levels in Adolescents at SMP Muhammadiyah 2 Gamping - Isneini Mewanda Putri; Luluk Rosida (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
Obesity is one of the nutritional problems commonly experienced by Indonesian adolescents. The negative impact of obesity is closely related to various serious diseases such as diabetes mellitus. Currently, adolescents can also suffer from diabetes mellitus just like adults. This study aims to determine the correlation between body mass index and random blood sugar levels in adolescents at SMP (Junior High School) Muhammadiyah 2 Gamping. This study method employed an observational analytic with a cross-sectional design. The population were 97 eighth grade students. The sampling technique employed proportionate stratified random sampling and number of samples was 49 students. Data collection performed using weight scales, stadiometers, digital glucometers, and observation sheets. The results of the univariate analysis showed that of the 49 respondents; the most body mass index was in the normal category (20 respondents (40.8%), and the most random blood sugar levels were in the prediabetes category (39 respondents (79.6%). The results of the correlation analysis with Spearman Rank obtained a p-value of 0.794 (>0.05) so it can be concluded that there is no relationship between body mass index and random blood sugar levels. However, students of SMP Muhammadiyah 2 Gamping are expected to continue to pay attention to their body health by consuming nutritious foods, living a healthy lifestyle, and doing regular physical activities.